A Systematic Review: Examining the Impacts of Artificial Intelligence - David Chow; Catharina Dwi Astuti Depari; Eva Gabriella (Journal of Artificial Intelligence in Architecture, 2026)
Since its breakthrough in the mid-20th century, Artificial Intelligence (AI) has held great promises for improving the capacity of urban planning to address complex problems. Despite this, the literature on how AI was specifically utilized and how it impacted urban planning remains limited. This study was aimed at examining how AI-driven technology shapes the landscape of urban planning. To attain this, we reviewed 48 articles after performing a systematic screening of 2,359 journal records in the Scopus database, published since the rising use of AI in urban planning. We found that urban planners have broadly adopted AI to address various complex environmental problems toward the making of sustainable and smart cities. Additionally, Machine Learning, Big Data, and the Internet of Things (IoT) are also indicated as AI-driven technologies commonly adopted in urban planning over the years.